2007
DOI: 10.1007/s11239-007-0026-8
|View full text |Cite
|
Sign up to set email alerts
|

Relation between impaired antiplatelet response to clopidogrel and possible pleiotropic effects

Abstract: Impaired antiplatelet response to clopidogrel but not to aspirin may contribute to smaller anti-inflammatory response in patients with ST-elevation myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Price et al observed no apparent benefit of a higher dose of clopidogrel (150 vs. 75 mg) in patients with HTPR ( 7 ). Moreover, a study conducted to demonstrate the potential additive predictive value of several platelet tests in the assessment of risk and/or recurrence of ischemic events concluded that platelet tests contributed a comparatively minor additive value to ischemic risk assessment in contrast to clinical and angiographic risk models ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Price et al observed no apparent benefit of a higher dose of clopidogrel (150 vs. 75 mg) in patients with HTPR ( 7 ). Moreover, a study conducted to demonstrate the potential additive predictive value of several platelet tests in the assessment of risk and/or recurrence of ischemic events concluded that platelet tests contributed a comparatively minor additive value to ischemic risk assessment in contrast to clinical and angiographic risk models ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In ACS patients undergoing PCI, hsCRP increased significantly at day 5 in clopidogrel naïve patients, but was reduced in patients on clopidogrel (Vivekananthan et al, ). Similarly, in low clopidogrel responders, hsCRP increased 7 days post PCI while in high responders, hsCRP remained within the reference intervals (Malek et al, ). In patients receiving long‐term clopidogrel therapy compared with the clopidogrel‐naive group, lower levels of selected inflammation markers (IL, TNF‐α and hsCRP) were achieved (Antonino et al, ).…”
Section: Effects On Inflammationmentioning
confidence: 94%
“…One of the other medications of some significant interest within the PFA-100 story is clopidogrel. The PFA-100 appears to be only mildly sensitive to clopidogrel, 99,[113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129] although several studies have shown clopidogrel to potentiate the effects of aspirin or other drugs on the PFA-100 CT and/or time dependence for clopidogrel sensitivity.…”
Section: Sensitivity Of the Pfa-100 To Clopidogrelmentioning
confidence: 99%